Cognitive Science and Hathayoga - Goldberg, Ellen (Zygon, 2005)
Abstract. Cognitive science and hathayoga both make emphatic claims about the relationship between the body and the mind. To examine this complementary relationship I draw upon the five main approaches currently being used by cognitive science and then consider their implications within the context of three specific points of contact with hathayoga theory: the rejection of dualism, the nature of consciousness, and the role of the nervous and circulatory systems in religious experience. This type of comparative analysis can provide additional information about the nature of consciousness and the potential practices that heighten our awareness or knowledge of it. Consequently, cognitive science offers a new and provocative way to dialogue with Indian yoga traditions in terms of the methods and theories of modernity.